A Strong Correlation Between the Severity of Flatfoot and Symptoms of Knee Osteoarthritis in 95 Patients - Zhang, Min; Nie, Mao-dan; Qi, Xin-zheng; Ke, Song; Li, Jun-wei; Shui, Yang-yang; Zhang, Zhuo-yue; Wang, Min; Cheng, Cheng-Kung (Frontiers in Surgery, 2022)
Objective: The purpose of this study is to assess the association between the presence and severity of flatfoot and symptoms of knee OA. Methods: 95 participants with knee OA were recruited from a patient cohort at a regional hospital. Symptoms of knee OA, including knee degeneration, femorotibial alignment, pain, stiffness and dysfunction were assessed using the Kellgren-Lawrence (K-L) grading system, femoral-tibial angle (FTA), and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Participants were divided into groups with flatfoot (mild, moderate and severe) and without flatfoot based on the Clarke’s angle. Linear regression and ordinal logistic regression were used for statistical analysis, as appropriate. Results: Having flatfoot was associated with a significantly increased risk of having a higher K-L grade (OR: 20.03; 95% CI: 5.88, 68.27; p < 0.001), smaller FTA (Beta: -2.96; 95% CI: -4.41, -1.50; p < 0.001), higher pain score (Beta: 0.47; 95% CI: 0.24, 0.69; p < 0.001) and greater loss of function (Beta: 0.25; 95% CI: 0.02, 0.48; p = 0.03). Severe grades of flat feet were associated with a higher K-L grade (OR: 0.19; 95% CI: 0.08, 0.44; p < 0.001), smaller FTA (Beta: 1.51; 95% CI: 0.66, 2.35; p = 0.001), higher pain score (Beta: -0.25; 95% CI: -0.39, -0.11; p = 0.001), greater stiffness (Beta: -0.24; 95% CI: -0.38, -0.09; p = 0.002) and greater loss of function (Beta: -0.27; 95% CI: -0.41, -0.14; p < 0.001). Conclusion: The results indicated that the severity of flattening is significantly associated with symptoms of knee OA. For the conservative management of knee OA, both flatfoot and its severity should be carefully considered.